(3GdJMbjb hGdHjGf aj TQM GdHQgGfs - (3CHh GdMSf Ydj Hf ESeGYjd GdUfgGLi GdJdcGJi GdeYQha HGdCHjGQis; (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3BNQgG (B:s
(3TQM eSCdI aTGai dSGf GdabgGA Cf NGQb GdELeGY jcaQ Edi BNQ GdeSCdI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs